2004
DOI: 10.1243/0957650042456953
|View full text |Cite
|
Sign up to set email alerts
|

Review of passive heat transfer augmentation techniques

Abstract: Heat transfer augmentation techniques (passive, active or a combination of passive and active methods) are commonly used in areas such as process industries, heating and cooling in evaporators, thermal power plants, air-conditioning equipment, refrigerators, radiators for space vehicles, automobiles, etc. Passive techniques, where inserts are used in the flow passage to augment the heat transfer rate, are advantageous compared with active techniques, because the insert manufacturing process is simple and these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
98
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 323 publications
(99 citation statements)
references
References 66 publications
0
98
0
1
Order By: Relevance
“…These benefits are its easy installation, low cost and low maintenance [4,8]. The resistance to heat flow in a heat exchanger is broken by the disturbance introduced to the flow by the twisted-tape and therefore allow more heat to be transferred [3,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…These benefits are its easy installation, low cost and low maintenance [4,8]. The resistance to heat flow in a heat exchanger is broken by the disturbance introduced to the flow by the twisted-tape and therefore allow more heat to be transferred [3,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…A Dewan et.al. [9]have shown that heat transfer passive augmentation are advantageous compared with active techniques, because the insert manufacturing process is simple and these techniques can be easily employed in an existing heat exchanger. In design of compact heat exchangers, passive techniques of heat transfer augmentation can play an important role if a proper passive insert configuration can be selected according to the heat exchanger working condition (both flow and heat transfer conditions).…”
Section: IImentioning
confidence: 99%
“…Compound methods are hybrid methods in which both active and passive methods are used in combination. Passive and active techniques that are used for heat augmentation of laminar flow have been discussed in detail by Bargles [1].These are effective but involve complicated design and hence have limited applications [1][2][3]. Heat augmentation can further increased by perforating the twisted tape with different shapes with different arrangement [3].…”
Section: Introductionmentioning
confidence: 99%